An Examination of Adolescent Girls' and Young Women's Entrepreneurial Knowledge in South Africa: Longitudinal Study - Jean Damascene MVUNABANDI; Bomi Cyril NOMLALA; Lawrence GADZIKWA (Indonesia Strategic Sustainability, 2023)
Motivated by lack of empirical research on entrepreneurial knowledge training among adolescent girls and young women in South Africa and elsewhere, this article examined the entrepreneurial knowledge among 3584 adolescent girls and young women from four provinces, namely KwaZulu Natal, Mpumalanga, Eastern Cape and Western Cape in South Africa. This study adopted quantitative and descriptive research approach. Secondary data collected using questionnaire survey during entrepreneurial mindset and skills training from July-October 2021 by the large anonymised not for profit organisation based in South Africa was used for data analysis. Robustness analysis was entirely performed using descriptive statistics using SPSS version 28.0. The findings from the empirical part of this research statistically proved the adolescent girls and young women improved their knowledge entrepreneurially after training that is evident in most extent literature. This article contributes to the current body of knowledge as it filled in the gap and contributed significantly to the entrepreneurial mindset skill and knowledge improvement among adolescent girls and young women in South Africa.